REPCOM: A Customisable Report Generator Component System - Leong, Chee Hoong; Lee, Sai Peck (Malaysian Journal of Computer Science, 2003)
This paper introduces a XML-driven and component-based development approach to report generation with the purpose of promoting portability, flexibility and genericity. In this approach, report layout is specified using a user-defined XML elements together with queries that retrieve data from different databases. A report is output as a HTML document, which can be viewed using an Internet browser. This paper presents the approach using an example and discusses the usage of the XML-driven report schema and how the proposed reusable report engine works to output an HTML report format. In addition, the tool is implemented to support heterogeneous database models. Overall, this system reduces the implementation cost and improves the productivity of work.